Investigation of the transient response of dynamic stress intensity factors to impact loads - Ng, Kok Kong. (2009)
Many spectacular failures have occurred in the engineering world where the failure of the structure occur very suddenly when it is not subjected to loads which is near the yielding stress and people always wonder why. The answer to such spectacular failure was only provided when the study of fracture mechanics evolved. This was when engineers start to realized that the inherent flaws in brittle materials have led to such failures which have brought about engineering disasters. This report mainly investigates the response of the stress intensity factors values for various problems using the Finite Element Method. The transient response of an infinite elastic plate that is weakened by a centrally located crack is considered. The calculation of the stress intensity factors are obtained from the crack tip at discrete times when pressure is suddenly applied to the surface of the plate. The plate in this study was modeled and the solution is obtained from the software ANSYS. The results of the simulations are presented in the results and discussion sections. The main factors that are examined are geometrical configuration, crack length and damping of the material.